An Ex Post Evaluation of Canadian Occupational Projections, 1961-1981 - Foot, David; Meltz, Noah (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
This paper presents a quantitative retrospective evaluation of three Canadian occupational projections covering the period 1961 to 1981 in an attempt to assess their usefulness as a guide to education and training policies. Using appropriately adjusted, detailed occupational data from the 1961, 1971 and 1981 Canadian censuses, the results indicate that for major occupational groups the projections were generally acceptable (within ± 10%) and that the use of variable coefficients can provide useful additional information for occupational projections.